2000
DOI: 10.1002/1521-4141(200010)30:10<2782::aid-immu2782>3.0.co;2-9
|View full text |Cite
|
Sign up to set email alerts
|

Anti-SSA/Ro52 autoantibodies blocking the cardiac 5-HT4serotoninergic receptor could explain neonatal lupus congenital heart block

Abstract: The 52‐kDa SSA/Ro (Ro52) ribonucleoprotein is an antigenic target strongly associated with the autoimmune response in mothers whose children develop neonatal lupus and congenital heart block. When sera from patients with systemic lupus erythematosus were used as autoimmune controls in an enzyme immunoassay to screen for antibodies against the human serotoninergic 5‐HT4‐receptor, a high correlation was found between the presence of anti‐Ro52 protein antibodies in such sera and antibodies reacting with a synthet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
58
0
2

Year Published

2001
2001
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 117 publications
(60 citation statements)
references
References 39 publications
(43 reference statements)
0
58
0
2
Order By: Relevance
“…This, together with the recent demonstration that the CYP2D6 molecule is expressed on the hepatocyte membrane and is targeted by LKM1 (37,38), suggests that this sequence may be directly involved in autoantibody mediated liver cell damage, akin to the scenario in myasthenia gravis (39), autoimmune thyroiditis (40), autoimmune thrombocytopenia purpura (41), hemolytic anemia (42), and neonatal systemic lupus erythematosus (43).…”
Section: Discussionmentioning
confidence: 99%
“…This, together with the recent demonstration that the CYP2D6 molecule is expressed on the hepatocyte membrane and is targeted by LKM1 (37,38), suggests that this sequence may be directly involved in autoantibody mediated liver cell damage, akin to the scenario in myasthenia gravis (39), autoimmune thyroiditis (40), autoimmune thrombocytopenia purpura (41), hemolytic anemia (42), and neonatal systemic lupus erythematosus (43).…”
Section: Discussionmentioning
confidence: 99%
“…The L-type Ca 2+ channel may not be the only target for maternal anti-SSA/Ro and/or SSB/La antibodies, because a specific cross-reaction between the recombinant 52kDa SSA/Ro protein and the second extracellular loop of serotoninergic 5-HT 4 receptor expressed in human atrial cells has been identified (sequence G21V) (Eftekhari et al, 2000). In contrast to the results describe above, anti-G21V affinity-purified autoantibodies from lupus patients or from rabbits immunized with the G21V peptide do not inhibit basal I CaL in adult human atrial myocytes.…”
Section: Congenital Heart Blockmentioning
confidence: 99%
“…In contrast to the results describe above, anti-G21V affinity-purified autoantibodies from lupus patients or from rabbits immunized with the G21V peptide do not inhibit basal I CaL in adult human atrial myocytes. However, these antibodies antagonize serotonin-induced activation of I CaL (Eftekhari et al, 2000;Salle et al, 2001); the authors hypothesized that during the early phase of fetal development the serotoninic pathway is more prominent than the β-adrenergic pathway so that 5-HT 4 receptor block leads to a reduction of I Ca which could in turn induce bradycardia and atrioventricular block .…”
Section: Congenital Heart Blockmentioning
confidence: 99%
“…32 Accordingly, it has been considered that disease-associated autoantibodies may emerge from the natural autoantibody repertoire. 33 In this context, characterization of agonistic anti-G protein-coupled receptor autoantibodies in several pathologic conditions, including Graves disease, 34 preeclampsia, 35 neonatal lupus congenital heart block, 36 and schizophrenia, 37 may presume that these kinds of autoantibodies, including anti-hMOR autoantibodies, are a common feature of the natural autoantibody repertoire.…”
Section: Discussionmentioning
confidence: 99%